Building Information Modeling (BIM) implementation - Quantity surveying firm practices for quality improvement / Mohd Esham Mamat, Shahela Mamter and Noor Anisah Abdullah - Mamat, Mohd Esham; Mamter, Shahela; Abdullah, Noor Anisah (2021)
Building Information Modelling (BIM) is a detailed process of designing and building in the construction industry collaboratively by usingan integrated system generated by computer. It provides a large amount of benefit in terms of cost and time saving, delivers much better accuracy in estimation and reduces arithmetical error which enables any amendment due to loss of information. Existing studies have determined the quantity surveying firm readiness due to BIM implementation in Malaysia. This research aimed to establish the readiness of BIM application in quantity surveying firms for quality improvement especially in current practices with undiscovering of present finding. The study objectives are to find out the importance of BIM in the construction industry, to investigate the challenges faced by quantity surveying firms in the implementation of BIM and to suggest a suitable solution for quality improvement to quantity surveying firms. The data collection was conducted by using the quantitative method of questionnaires. The scope is narrowed down to quantity surveying firms that are registered in Board of Quantity Surveyors Malaysia (BQSM) at Northern Region of Peninsular Malaysia only. The findings of this study reveal that quantity surveying firms had difficulties in implementing BIM because of lack capability and the complexity of using BIM software itself such as Cubicost by Glodon. Findings also indicate that the difficulties of collaboration in implementing BIM software have caused the firms to decline in using the software and the implementation of BIM software requires the participation of all parties who are involved in the project such as the architect and the engineer. Hopefully, this research will help the quantity surveying firm to implement BIM in their current practices for quality improvement by highlighting its effectiveness.